2015 International Conference on Pervasive Computing (ICPC) 2015
DOI: 10.1109/pervasive.2015.7086972
|View full text |Cite
|
Sign up to set email alerts
|

User identity and Access Management trends in IT infrastructure- an overview

Abstract: Nowadays, people around the world completely depend and mostly use the Internet to maintain communication, contact with family, friends and with people around the world, access and exchange information, and enjoy multimedia communication. As the use of internet increase then users those who use internet and Access the information using internet in the organization or outside organization also increase. User Data security is very tedious and important part of IT system and its user lifecycle control system. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…2 Literature review Thakur and Gaikwad (2015) identified the identity management IM as emerging technologies process which enables managing the required information about the identity of the user; also it provides control access to organization available resources. They summarized the main function of IM system by improving productivity and providing security with the lowest costs involved in managing user attributes and credentials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Literature review Thakur and Gaikwad (2015) identified the identity management IM as emerging technologies process which enables managing the required information about the identity of the user; also it provides control access to organization available resources. They summarized the main function of IM system by improving productivity and providing security with the lowest costs involved in managing user attributes and credentials.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the general IAMS architecture, as we can notice that the server of WebSphere application is the main part of this architecture. Source: Thakur and Gaikwad (2015) According to Yang et al (2014), IDAM techniques can be basically characterized by the access decision basis, as explained in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the access to an identity by the right user at the right time is also taken care of in Access Management [1]. Access management in public and private networks is a serious concern in the field of Information Technology.…”
Section: Introductionmentioning
confidence: 99%